Evaluation of radiation stability of electron beam irradiated Nafion® and sulfonated poly(ether ether ketone) membranes. (June 2022) - Pajuste, E.; Reinholds, I.; Vaivars, G.; Antuzevičs, A.; Avotiņa, L.; Sprūģis, E.; Mikko, R.; Heikki, K.; Meri, R.M.; Kaparkalējs, R.
Highlights: Effects of electron beam radiation on the physico-chemical and mechanical properties of two types of proton exchange membranes - commercial NafionⓇ117 and sulfonated poly(ether-ether-ketone) (SPEEK) with high degree of sulfonation (DS = 0.75±0.5), has been estimated. The advantages of SPEEK membrane materials for applications in ionizing radiation environments are demonstrated. The ionising radiation modified NafionⓇ shows reduced thermal and mechanical stability compared toSPEEK membranes. Abstract: Proton exchange membranes (PEM), which have been commonly used in fuel cells have raised interest for the application in harsh environments involving ionizing radiation. Therefore, radiation stability and ability to sustain their functionality under the radiation environment are of great interest. Within this study, electron beam irradiation in dose range from 50 to 500kGy was used to evaluate the effects of radiation on the physico-chemical and mechanical properties of two types of PEM: commercial Nafion®117 and sulfonated poly(ether-ether-ketone) (SPEEK) with high degree of sulfonation (DS = 0.75±0.5). SPEEK membrane presented higher mechanical and thermal stability compared to that of Nafion® at doses up to 250 kGy, which was evidenced by infrared and electron paramagnetic resonance spectroscopy, thermal analysis, ion chromatography methods. Tensile tests at room temperature and dynamical mechanical analysis of irradiated membranes revealed improved strength, storage modulus at room and elevated temperatures (80°C) for irradiated SPEEK as compared to pristine PEM. For comparison Nafion® exhibited notable deterioration of mechanical properties including elongation at break due to the predominant oxidation and chain scission already at doses exceeding 50 kGy. The study indicated that SPEEK could be perspective replacement of traditional PEM for application in fuel cells exposed to ionising radiation.